Microbial metabolite oxindole curbs acute lung injury by suppressing CXCL13 - Shixin Tang; Jun Zhang; Zhenghai He; Gang Liu; Shenyou Nie; Xingyang Shi; Kun Zhang; Dandan Pi; Xiao Gui; Yi He; Shuang Zhao; Zhihui Liu; et al. (Proceedings of the National Academy of Sciences, 2026)
The gut–lung axis is involved in acute lung injury (ALI) and its fatal sequela, acute respiratory distress syndrome (ARDS), yet the molecular mechanisms governing this crosstalk remain poorly defined. Untargeted metabolomics of plasma revealed significant dysregulation of tryptophan metabolism in ARDS patients compared to healthy controls. Murine dietary interventions demonstrated that high tryptophan intake alleviated ALI severity, whereas deficiency exacerbated injury, with protection being gut microbiota dependent. 16S ribosomal RNA (16S rRNA) gene sequencing revealed marked depletion of a functionally central bacterium Lactobacillus johnsonii ( L. johnsonii ) during ALI. Supplementation with L. johnsonii or its encapsulated form attenuated ALI, but this required dietary tryptophan sufficiency. Mechanistically, L. johnsonii converts tryptophan into oxindole, which enters pulmonary macrophages, promotes the aryl hydrocarbon receptor-RelA binding, and thereby suppresses RelA-mediated transcriptional activation of C-X-C motif chemokine 13 (CXCL13). Both genetic ablation and pharmacological inhibition of CXCL13 ameliorated ALI symptoms. Importantly, oxindole and CXCL13 levels correlated with ARDS severity in patients, suggesting their clinical relevance. Collectively, these findings define a protective microbiota-dependent gut–lung axis in ALI/ARDS that is mediated by dietary tryptophan-derived oxindole, which acts at least partially through CXCL13 suppression to underscore targetable diet–microbe–metabolite therapeutic paradigms.